Pengaruh Model Think Pair and Share (TPS) Terhadap Hasil Belajar Siswa Kelas IV SD Negeri 0510 Sihiuk - Hasibuan, Nur Kholilah; Harahap, Nurhalimah; Saputra, Rizki Hamdan (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study aims to determine the effect of the think pair and share model on the learning outcomes of grade IV students of SD Negeri 0510 Sihiuk. This study used quantitative research with an experimental research approach with a one group pretes-posttes research design model. The population of this study was all grade IV students at SD Negeri 0510 Sihiuk, and the sample of this study was determined by population, namely all grade IV students of SD Negeri 0510 Sihiuk, Lubuk Barumun District, Padang Lawas Regency, totaling 35 students. Data collection is carried out by tests and documentation with data analysis techniques, namely descriptive statistics, normality tests, homogeneity tests, linearity tests and T tests. Based on the results of data analysis, it was concluded that the average pretest score was 50 and the average posttest score was 71. There is a significant influence of Think Pair and Share (TPS) Model Learning in Improving Student Learning Outcomes in Science Subjects. This is evidenced by calculations carried out using the t test showing that the tcount > ttable is (1 < 2.48). This means that there is an influence of the Think Pair and Share (TPS) learning model on student learning outcomes in Class IV science subjects SD Negeri 0510 Sihiuk.